Pelatihan Pengembangan Bahan Ajar BIPA Berbasis Budaya dan Tradisi Siam di Thammasat University, Thailand - Tri Murwaningsih; Kundharu Saddhono; Budi Legowo; Hamam Supriyadi; Aldi Dwi Saputra (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
Indonesian for Foreign Speakers (BIPA) serves as a strategic medium for introducing the Indonesian language and culture to the international community while supporting the internationalization of the Indonesian language. One of the major challenges in BIPA instruction is the availability of contextual teaching materials that accommodate learners' cultural backgrounds. To address this issue, a training and mentoring program on the development of culture-based BIPA teaching materials integrating Thai and Indonesian cultures was conducted for students and instructors at Thammasat University, Thailand. The program employed a hybrid learning model consisting of six months of online mentoring followed by a seven-day face-to-face workshop. The methods included lectures, group discussions, workshops, hands-on material development, intensive mentoring, presentations, and evaluation. The results demonstrated a significant improvement in participants' understanding and skills in developing culture-based BIPA teaching materials. The primary output of the program was a textbook entitled Mari Belajar Bahasa Indonesia: Buku Ajar BIPA Tingkat Dasar Berbasis Budaya Thailand dan Indonesia, which presents fundamental Indonesian language materials within the cultural contexts of both countries. The textbook was designed to support contextual, communicative, and intercultural BIPA learning for beginner-level learners. Furthermore, the program strengthened the academic partnership between Universitas Sebelas Maret and Thammasat University as an implementation of the Sustainable Development Goals (SDGs), particularly SDG 17 (Partnerships for the Goals), through international collaboration in educational development and language diplomacy. Therefore, the program contributes to improving the quality of BIPA instruction, strengthening international academic cooperation, and promoting the Indonesian language and culture at the global level.